N1 lymph node detection in lymph node harvesting in non-small cell lung cancer: Formaldehyde exposure is a drawback? - Sevinc Citak; Talha Dogruyol; Serkan Bayram; Mustafa Vayvada; Serda Kanbur Metin; Volkan Baysungur (Journal of Cardiothoracic Surgery, 2023)
Abstract Objective This study aimed to evaluate the effect of lymph node dissection method on staging results, diagnosis of tumor metastasis in single or multiple N1 lymph nodes and survival rates in patients with non-small cell lung cancer (NSCLC). Methods Patients with NSCLC who underwent anatomic resection between September 2014 and October 2019 were examined prospectively. All patients with similar clinico-demographic characteristics were randomly assigned to either the surgical group (n = 83) or the pathology group (n = 87). Lymph node dissection was performed by the surgeon in the surgical group and by the pathologists after formaldehyde exposure in the pathology group. Data were analyzed according to formaldehyde exposure, N1 positivity, and number of N1 positive lymph nodes. Results There were no significant differences in N1 lymph node positivity between the two groups (p = 0.482). On average 9.08 lymph node sampling was performed in the surgical group and 2.39 in the pathology group (p = 0.0001). Multiple lymph node involvement was significantly higher in the surgical group (P = 0.0001) than in the pathology group. Conclusion It is easier to detect lymph node involvement without introducing formaldehyde into the sample. We recommend that N1 lymph node dissection be performed on fresh specimens to detect more lymph node involvement.